Breast Cancer Detection - Soni Ahirrao; Vinanti Bhoeer; Shivani Patil; Himani Jawale (International Journal of Engineering and Management Research, 2020)
Breast Cancer is highly predominant in women in today’s world. It starts in the breast during the initial stages and spreads to other areas of the body after some period of time. Breast cancer is the second-largest disease leading to the death of women. The disease is curable if detected early enough. Breast Cancer Application monitors the abnormal growth of breast cells during the early stages. They are often diagnosed during the advanced stages of breast cancer. It is the second most diagnosed cancer in women, affecting one in every eight women. Our project comprises two modules, first consists of an application with user login and self-test examine section where and the second section consists of identifying benign and malignant cells. The second section will be used by doctors' side for the detection of abnormalities of breasts as early as possible by providing the user screening data set. It contains Machine Learning techniques for the classification of malignant and benign tumors. There are more treatment options and a better chance of survival. If breast cancer is detected during the early stages then there is a 93 percent of higher survival rate in the first five years.